Perbandingan antara Rasio Neutrofil Limfosit dan Trombosit pada Kebocoran Plasma Anak - Sembiring Meliala, Fransisco Aditia; Silaen, Johan Christian; Simanjuntak, Novita Hasiani (Nommensen Journal of Medicine, 2021)
Background: Dengue virus infection is a global health problem. Dengue Hemorrhagic Fever (DHF) has become a global attention because of children death due to plasma leakage. Plasma leakage is a symptom of critical phase in children that occurs on the 3rd to 5th day. Neutrophil lymphocyte (NL) ratio and platelet count change can be seen in critical phase of plasma leakage which can help process of patient’s therapy. Objective: This study aimed to compare the NL ratio and platelets count on plasma leakage in children with DHF. Methods: This study was an analytical study with cross-sectional design. The sample was children with DHF at RSUD Dr.Pirngadi Medan. The data of this study were analyzed by computer software, used an unpaired t test with p <0.05. Results: This study found that the most age of DHF was 6-10 years old, most gender are male and DHF grade 1. Unpaired t test found the average difference between NL ratio and platelet with value of p = 0.043 (p<0.05). Conclusion: Plasma leakage average on NL ratio is higher than plasma leakage average on platelets that occurs in children with DHF at RSUD Dr.Pirngadi Medan.